Merry Madagascar - DreamWorks Home Entertainment (Firm) ([United States] : DreamWorks Home Entertainment, 2009)
"When Santa and his reindeer crash onto the island of Madagasgar, it's up to Alex, Marty, Gloria, Melman and those wacky penguins to save Christmas"--Container.
MPAA rating: Not rated.
DVD, region 1, widescreen (1.85:1) ; full screen (1.33:1) presentation; Dolby Digital 5.1, Dolby Digital 2.0 stereo., single sided, dual layer.
English, dubbed French or dubbed Spanish dialogue, English, French or Spanish subtitles; closed-captioned.
Keywords: Zoo animals -- Madagascar -- Juvenile drama; Holidays -- Juvenile drama; Feature films; Animated films; Christmas films; Children's -- Animation -- Feature; Video recordings for the hearing impaired